Medical student stress during the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: Evaluate the stress of medical students facing the COVID-19 pandemic. Method: Quantitative, observational, cross-sectional study. 320 students regularly enrolled in the medical course of any Brazilian Higher Education Institution (HEI) participated in the research, from the first to sixth year, in legal age. Data collection was carried out online, with the sending of a link to access the self-administered survey instrument, containing questions about the sociodemographic profile and lifestyle and the Perceived Stress Scale. The research was approved by the Research Ethics Committee of the Universidade do Planalto Catarinense (number 072659/2020). Data were then submitted to descriptive statistical analysis. Results: The pandemic negatively impacted the lifestyle of students, who reduced the practice of physical activities and worsened their diet. Also, 46.6% of the students had a problem or development of psychopathological anxiety disorder. Through the Perceived Stress Scale, it was observed that the vast majority of medical students (75.6%) had an average stress level (31±4). Conclusion: The COVID-19 pandemic impacted negatively medical students, making them more anxious and stressed. It is necessary to implement mental health support networks in universities for these students. In addition, greater support is also needed for the student in returning to practical activities, with the correct supply of all PPE and greater training to face COVID-19.